Radial Forearm Free Flap Reconstruction of Glossectomy Defects Without Tracheostomy. (June 2022) - Wu, Tara J.; Saggi, Satvir; Badran, Karam W.; Han, Albert Y.; Sand, Jordan P.; Blackwell, Keith E.
Objectives: To assess the feasibility of radial forearm free flap (RFFF) reconstruction of glossectomy defects without tracheostomy tube (TT). Methods: Retrospective review of patients with at least oral tongue defects who underwent RFFF reconstruction. Pre- and intra-operative factors were documented. Post-operative respiratory complications included inability to extubate, pneumonia, or need for re-intubation or TT within 30 days. Results: Twenty-one patients underwent RFFF reconstruction without TT, and 36 patients with TT. The average hospital length of stay was 1.5 days shorter in those without TT ( P < .01). Two patients who underwent TT placement experienced a respiratory complication ( P = .27). There were no respiratory complications among those without TT. After multivariate analyses, large tongue base defect (>25% resection, P < .001) and bilateral neck dissection ( P < .001) were independently associated with TT placement. Conclusions: In our experience, RFFF reconstruction of glossectomy defects is feasible without TT among selected patients with small tongue base defects (≤25% resection) and unilateral neck dissection.